Verification of WRF-ARW convective-resolving forecasts over Southeastern SouthAmerica - Matsudo, Cynthia Mariana (2015)
During November-December 2012, high-resolution (4 km-38 vertical levels), convection-12 allowing 48 hours WRF-ARW forecasts were produced at the National Weather Service of 13 Argentina. The aim of this paper is to evaluate hourly quantitative precipitation forecasts to 14 assess the model performance on representing its location, intensity, spatial variability and 15 diurnal cycle. The focus is on the central-east region of Argentina and south of Brazil. The study 16 is based on a combination of visual comparison of forecasted and estimates accumulated 17 precipitation fields and objective scores calculated employing 8-km resolution CMORPH (CPC 18 MORPHing technique) satellite rainfall estimations. Additional insight is gained by examining 19 an organized convective event occurred during 6th and 7th December 2012. As a complement, 20 radar data is considered to evaluate convective features using simulated model reflectivity. 21 Results show that WRF model forecast captures quite well the position and timing of the major 22 convective events, even though the magnitude of events was underestimated. Total amounts 23 averaged over the verification domain are underestimate as well as the areal coverage for 24 small thresholds. In general, results suggest that convection-allowing WRF-ARW model has the 25 potential to improve short range forecasts over the region although it should be evaluated 26 over a longer period of time.